THE EFFECTIVENESS OF TEACHING WRITING BY USING FRAYER MODEL TO THE EIGHTH GRADE OF SMP NEGERI 2 PAGARALAM - Tri Rohani (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
This study aims at finding the significant difference in writing achievement in descriptive text between the students who were taught by using Frayer Model and those who were not of the eight grade students of SMP Negeri 2 Pagaralam. The methodology of the research was quasi experimental research. The findings related the research questions showed that the value of t-obtained was 7.395, at the significance level .000., in two tailed testing with df = 58, the critical value of the t-table was 2.045. Since the value of t-obtained was higher than the critical value of t-table, the null hypothesis (H0 ) was rejected and the alternative hypothesis (Ha ) was accepted. The result revealed that the pre-test and the post test showed such a meaningful outcome where in the pre-test of experimental class most of students were in poor level, while in the post test most of students achieved enough level. It means there was significant difference in students writing achievement in descriptive text between the students who were taught by using Fayer Model and those who were not of the eighth grade students of SMP Negeri 2 Pagaralam. It implies that frayer model was effective to improve students writing skill especially in exploring their thoughts or ideas.